(untitled) (Revista Apotheke, 2019)
: I present the urban intervention “Bonecas Trapeiras” (Rags Dolls, 2019) and its repercussions in the field of training visual arts teachers who work with children. I report teaching and learning processes shared with students of the Visual Arts Degree Course at the Universidade Federal de Pernambuco, in the perspective of Visual Culture Education for teacher education. I build an affective map of autobiographical narratives with clues to remember our own childhoods, with poets and artists who believe in walking as an aesthetic practice and overflowing in the processes of creation and urban intervention “Rags Dolls”, held in 2019.